[Offloading of sugar cane] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Cane offloaded at the Number one Tandem Road cane hoist (the tipper).
Cataloger's title
Keywords: Sugarcane -- Trinidad and Tobago